Authority, Gender and Emotions in Late Medieval and Early Modern England - Broomhall, Susan. author. aut Link
XVI, 229 p.
Keywords: This collection explores how situations of authority, governance, and influence were practised through both gender ideologies and affective performances in medieval and early modern England. Authority is inherently relational it must be asserted over someone who allows or is forced to accept this dominance. The capacity to exercise authority is therefore a social and cultural act, one that is shaped by social identities such as gender and by social practices that include emotions. The contributions in this volume, exploring case studies of women and men's letter-writing, political and ecclesiastical governance, household rule, exercise of law and order, and creative agency, investigate how gender and emotions shaped the ways different individuals could assert or maintain authority, or indeed disrupt or provide alternatives to conventional practices of authority.